DIGITAL MEDIA-BASED LEARNING IN THE INDEPENDENT CURRICULUM AT NASIMA ELEMENTARY SCHOOL - Jauhari, Angelita Mustika; Hanik, Elya Umi; Ainuha, Husnunnadia Fitria; Andriana, Rizka (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Digital media-based learning is one of the innovations in the Merdeka Curriculum which aims to improve the quality of education by using technology. SD Nasima as one of the schools implementing the Merdeka Curriculum has integrated various digital media in the learning process to support 21st century skills, such as critical thinking, creativity, communication, and collaboration. This study aims to analyze the application of digital media in learning at SD Nasima, its impact on student learning outcomes, and the challenges faced in its implementation. The research method used is a qualitative descriptive study with data collection techniques through observation, interviews, and documentation. The results of the study show that digital media-based learning in the Merdeka curriculum at SD Nasima includes Smartboard, Interactive Learning Panel, Educational Applications. However, the use of digital media certainly has advantages and obstacles faced.